The relationship between HRM practices, leadership style, affective commitment and informal workplace learning - Khandakar, Md. Shariful Alam (2018)
Informal workplace learning is considered as one of the progressively important issues in the contemporary global business environment. Although informal workplace learning is an important issue, there is a lack of such learning in private commercial banks (PCBs) in Bangladesh. Based on the theory of situated learning which argues that organizational factors and personal factors influence workplace learning, the study aimed to examine the relationship between human resource management practices (HRM), leadership style and informal workplace learning. The study also considered the mediating effect of affective commitment on this relationship. A quantitative research technique was applied and a structured questionnaire was used as the research instrument. A cross sectional survey design was adopted and the unit of analysis was employees working as head of department in branches of PCBs. The study employed the probability sampling technique, with a sample size of 381. The Partial Least Squares to Structural Equation Modelling (PLS-SEM) approach was applied for analyzing the data. The findings suggest that HRM practices such as selective hiring, extensive training, performance appraisal, compensation practices, empowerment, information sharing and leadership style such as transformational leadership style are the strong predictors of informal workplace learning. Employment security and promotion opportunities have no significant impact on informal workplace learning. In addition to that, affective commitment mediates the relationship between HRM practices such as, extensive training, compensation practices, promotion opportunities, empowerment, information sharing and informal workplace learning. Similarly, affective commitment also mediates the relationship between transactional leadership style and informal workplace learning. Based on the empirical evidences, practitioners and policy makers should pay more attention to HRM practices and leadership style for enhancing informal workplace learning.